A preliminary investigation of the properties of plantain starch-chitosan composite films containing Panadol leaf extracts - Chad Lafeuillee; Rohanie Maharaj (Discover Food)
Abstract The study explores composite polysaccharide films made from plantain pulp starch and chitosan, incorporating extracts from Panadol leaves of Plectranthus barbatus and Plectranthus caninus to improve physicochemical and antimicrobial properties. Plantain pulp starch was extracted using 25% NaOH and films were created via solvent casting by combining equal volumes of 5% starch and 2.5% chitosan. Phytochemical screening of the ethanolic leaf extracts employed spectroscopic methods. Evaluations included antioxidant capacity, total phenolic and flavonoid contents, water solubility, swelling indices, water vapour transmission rates and optical properties. Antimicrobial activity was tested using the disk diffusion method and plate count agar. Antioxidant activities showed % DPPH inhibition of 74.60 ± 0.05 and 64.77 ± 0.07 for Plectranthus barbatus and Plectranthus caninus, with phenolic contents of 86.56 ± 0.03 and 69.59 ± 0.04 mg/g gallic acid equivalents, and flavonoid contents of 91.25 ± 0.005 and 74.49 ± 0.003 mg/g quercetin equivalents respectively. The composite films exhibited increased opacity, density and moisture content alongside decreased swelling indices. Water solubility varied by component with no significant difference in water vapour transmission rates among the films. Both gram-positive and gram-negative bacteria were inhibited by the leaf extracts. The starch-chitosan composite films with leaf extracts demonstrated enhanced physicochemical and antimicrobial properties making them suitable for sustainable food packaging.